Implant surface features as key role on cell behavior - De Molon, Rafael Scaf [UNESP]; Pereira, Marta Maria Alves [UNESP]; De Avila, Erica Dorigatti [UNESP] (Tech Science Press, 2022)
It has been recognized that physical and chemical properties of biomaterial surfaces mediate the quality of extracellular matrix (ECM) that may affect cell behaviors. In nature, ECM is a heterogeneous three-dimensional superstructure formed by three major components, glycosaminoglycan, glycoconjugate, and protein, that anchors cellular compartments in tissues and regulates the function and the behavior of cells. Changes in the biointerface alter the quality of ECM and morphology through cell surface receptors, which, in turn, enable it to trigger specific cell signaling and different cellular responses. In fact, a number of strategies have been used to improve the functionality of surfaces and direct cell behavior through precisely designed environments. Herein, we aimed to discuss, through a science-based viewpoint, the biomaterial surface features on cell behavior and analyze the impact of cell physical modification on dental implant development.
Keywords: Biomaterial; Cell adhesion; Surface chemistry; Surface topography